Outcomes of robotic liver resections for colorectal liver metastases. A multi-institutional analysis of minimally invasive ultrasound-guided robotic surgery. (March 2019) - Guerra, Francesco; Guadagni, Simone; Pesi, Benedetta; Furbetta, Niccolò; Di Franco, Gregorio; Palmeri, Matteo; Annecchiarico, Mario; Eugeni, Emilio; Coratti, Andrea; Patriti, Alberto; Morelli, Luca
Abstract: Background: Current evidence supporting robotics to perform minimally invasive liver resection is based on single center case series reporting surgical outcomes in heterogeneous groups of patients. On the contrary, relatively scarce data specifically focusing on secondary hepatic malignancies is available. The objective of this study is to assess short- and long-term outcomes following liver resection for colorectal liver metastasis on a multi-institutional series of patients. Methods: All consecutive patients undergoing robotic surgery for colorectal liver metastasis at three different tertiary hospitals over a 10-year time frame were included in this analysis. All patients received ultrasound-guided liver resection according to tumor location following the principle of parenchymal sparing surgery. Perioperative, clinicopathologic and oncological outcomes were assessed. Results: A total of 59 patients underwent liver resection. There were 7 cases of conversion to open surgery. The postoperative complication rate was 27%, 5% being the rate of major morbidity. Overall, the mean postoperative hospital stay was 6 days and no mortality occurred. R0 resection was achieved for 92% of lesions. At a mean follow-up of 19 months, the 1-year and 3-year DFS was 83.5% and 41.9%, while the 1-year and 3-year OS was 90.4% and 66.1%, respectively. Conclusions: Robotic liver surgery does not impair surgical outcome and oncological results in patients with liver metastases from colorectal cancer. Highlights: Scarce data is currently available on the outcomes of robotic liver resection for colorectal liver metastases. A consecutive series of robotic surgery has been investigated in terms of both surgical and oncological data. Robotic technology may be employed to resect colorectal liver metastases competently.